Original paperTemperament and character profiles of patients with chronic idiopathic urticaria - Alan, Sevil; Canan, Fatih; Karakaş, Ayşe Akman; Geçici, Nihal (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Psychosocial factors have been implicated as being important in the onset and/or exacerbation of urticaria. Aim : To examine both personality factors of patients with chronic idiopathic urticaria (CIU) and the correlations between illness duration, severity of itching, urticaria activity score (UAS) and temperament-character dimensions. Material and methods: A total number of 70 CIU patients and 60 healthy individuals were included in the study. The Temperament and Character Inventory (TCI) was administered individually. The relationship between UAS, illness duration and severity of pruritus and TCI subscales were evaluated. Results : The CIU group had significantly higher scores of novelty seeking and lower scores of cooperativeness, reward dependence and self-directedness than the control group. Conclusions : The current study shows that CIU patients have distinctive temperament and character dimensions when compared with the control group. We suggest that evaluation and treatment of CIU should also include psychosomatic approaches in clinical practice.